From transition management towards just transition and place-based governance. Τhe case of Western Macedonia in Greece - Lefteris Topaloglou; Lefteris Ioannidis (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: This paper examines to what extent the governance modes of transition in the region of Western Macedonia (Greece) are effective and just, and whether they embed transition management, spatial justice, and place-based elements. To this end, the hypothesis tested in this paper is that spatial justice and place-based policy can make a positive contribution to just and well-managed transition. In this framework, the question examined is not about ‘who is in charge for designing and implementing transition policies?’ but about ‘what is the balance and mix of transition policies at the central, regional, and local levels of administration?’. METHODOLOGY: The article critically discussed the concept of transition as a fundamental societal change through the lens of efficiency and justice. Thus, the notions of transition management and spatial justice are thoroughly explored. It also embeds the concept of ‘place’ in this discussion. Therefore, the challenges, opportunities, and shortcomings of the place-based approach in the course of transition are examined. The empirical section contains a mix of quantitative and qualitative methods, such as the use of questionnaires and focus group meetings, preceded by background research, comprising mainly desk research. The above different cases of empirical work are not entirely irrelevant to each other. The validity of the research findings is strengthened by using multiple sources of evidence and data triangulation. The analysis at the empirical research level focuses on Western Macedonia in Greece. This region has all the characteristics of a coal-dependent locality, under an urgent need to design and implement a post-lignite, just, transition strategy. FINDINGS: Given that transition implies a profound and long-lasting societal, economic, and environmental transformation, new and pioneering modes of governance are necessary to tackle such a multifaceted challenge. The discourse about place, policies, and governance, reveals the need for focusing on a balance and mix of inclusive and multi-scalar policies instead of defining governance structures and bodies in charge for implementing transition policies. The launched transition governance model in Greece considerably deviates from the EU policy context. In fact, substantial shortcomings in terms of legitimacy, inclusiveness, and public engagement and overall effectiveness have been recorded. The empirical evidence reveals a rather clear top-down model than a hybrid one. The findings show that the governance model employed in the case of Western Macedonia, neither embeds spatial justice nor incorporates a place-based approach. IMPLICATIONS: Viewing the long-term process of transition through the lens of governance and policymaking, this paper challenges the assertion that the traditional top-down governance model is the most effective and fair approach. In this setting, the notions of transition management and spatial justice are thoroughly explored. The concept of ‘place’ is also embedded in this discussion. To this end, the challenges, opportunities and shortcomings of the place-based approach are analysed. Given that transition is by nature a multifaceted, multi-level and multi-actor process, an effective and just transition governance should reflect the views of different actors. In this sense, it seems that multi-level governance models for regions in transition need to harness existing interactions among different levels and actors. ORIGINALITY AND VALUE: After having touched upon the process of transition regarding the notions of ‘management’ and ‘justice,’ we embed the concepts of spatial justice and the place-based approach into governance transition practices. In this respect, the gap between efficiency and equity, redistributive logic (needs, results), and development policy (inclusive development) can be bridged through the so-called ‘spatial-territorial capital’ and spatially just, multi-level governance.